"Preemptive Participation" and Environmental Awareness Across Indian Water Quality Policy. (September 2017) - Kedzior, Sya Buryn
Public participation in environmental decision making is promoted in the Global South as a core tenet of "good governance" associated with sustainability. This emphasis on participatory governance has produced significant attention to the importance of "environmental awareness" as a precondition of participation in environmental governance. This article analyzes the connected discourses surrounding environmental awareness and participation in Indian water-quality policy, focusing on North India's Ganges River. Drawing on evidence from policy documents and interviews with government officials and other key informants, it argues that the emphasis on environmental awareness as a precondition of participation has allowed the state to effectively forestall participation, to approach awareness raising as a consensus-building activity, and to effectively rollback the regulation of polluting industries. Moreover, conditional participation has increased opportunities for state agencies to control the conditions and terms of "awareness, " contributing to the effacement of alternative environmental knowledges.